Module Based on Metacognitive Strategies to Reduce Misconceptions on Salt Hydrolysis Material - Rohmah, Datin Mufidhatur; Yuliani; Azizah, Utiya (Indonesia Approach Education, 2023)
The use of modules allows students to learn independently according to their abilities and interests, but it can also develop the ability to interact directly with the environment and other learning resources. This study aims to produce a module based on metacognitive strategies to reduce misconceptions on salt hydrolysis material. This research is a Research and Development by adapting the research and development stages modified by Sukmadinata with one group pretest-posttest design which is treated with a limited trial sample of 20 students of class XI MIPA at SMAN 1 Lamongan. The research instrument used was students' conception test sheets given before and after learning with the number of items, namely 5 reasoned multiple-choice questions accompanied by CRI (Certainty of Response Index). The results showed that in the concept of the hydrolysis reaction there was a change in misconception (MK) to know the concept (TK) by 74%, to not know the concept (TTK) by 0%, and still have a misconception (MK) by 26%. In the concept of salt solution pH there is a shift to TK, TTK, and MK respectively by 50%, 0%, and 50%. Thus, it can be concluded that modules based on metacognitive strategies can reduce misconceptions about the concept of hydrolysis reactions by 74% and about the concept of pH of salt solutions by 50%.